A Novel Function of Pet54 in Regulation of Cox1 Synthesis in Saccharomyces cerevisiae Mitochondria - Mayorga, Juan Pablo (J Biol Chem, 2016)
Cytochrome c oxidase assembly requires the synthesis of the mitochondria-encoded core subunits, Cox1, Cox2, and Cox3. In yeast, Pet54 protein is required to activate translation of the COX3 mRNA and to process the aI5β intron on the COX1 transcript. Here we report a third, novel function of Pet54 on Cox1 synthesis. We observed that Pet54 is necessary to achieve an efficient Cox1 synthesis. Translation of the COX1 mRNA is coupled to the assembly of cytochrome c oxidase by a mechanism that involves Mss51. This protein activates translation of the COX1 mRNA by acting on the COX1 5′-UTR, and, in addition, it interacts with the newly synthesized Cox1 protein in high molecular weight complexes that include the factors Coa3 and Cox14. Deletion of Pet54 decreased Cox1 synthesis, and, in contrast to what is commonly observed for other assembly mutants, double deletion of cox14 or coa3 did not recover Cox1 synthesis. Our results show that Pet54 is a positive regulator of Cox1 synthesis that renders Mss51 competent as a translational activator of the COX1 mRNA and that this role is independent of the assembly feedback regulatory loop of Cox1 synthesis. Pet54 may play a role in Mss51 hemylation/conformational change necessary for translational activity. Moreover, Pet54 physically interacts with the COX1 mRNA, and this binding was independent of the presence of Mss51.